Complex physical rehabilitation for patients of elderly age attached to stable stenocardia of tension on the stationary stage - Добрицька [Dobritskaya D.], Д. В. (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Special reference literature on the problem of utilization of the physical rehabilitation means for patients of elderly age attached to stable stenocardia of tension. The program of physical rehabilitation is made for patients of elderly age attached to stable stenocardia of tension on the stationary stage, which includes a remedial gymnastics, massotherapy and physiotherapy. The basic methods of medical physical culture are given for patients who are ached by a stable stenocardia of tension on the stationary stage of rehabilitation. The methods of valuation of effectiveness of physical rehabilitation attached to stable stenocardia of tension on the stationary stage. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->